The UNDRIP: an increasingly robust legal parameter. Issue 1 (7th February 2019) - Gómez Isa, Felipe
ABSTRACT: Indigenous peoples have lived through a process of invisibility and systematic exclusion practically ever since the era of conquest. The arrival of republican States in Latin America following the decolonisation process did not involve a substantial change in the traditional relationship of subjection and submission endured by native peoples in the Americas. In the mid-twentieth century, the international community began to pay attention to the marginalised situation of indigenous peoples. The main objective was to integrate some peoples that were considered to be backward and in need of protection. It was within this paradigm that most of the interactions with indigenous peoples have occurred, such as the first international treaty adopted in this field, Convention No. 107 of the International Labour Organisation (ILO, 1957). This situation began to change with the adoption of Convention No. 169 by the ILO in 1989, and especially with the recently adopted United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP, 2007). The UNDRIP has to be seen as the culmination of a long and difficult journey in which indigenous peoples themselves and their representatives have been key participants. Irrespective of the uncertain legal nature of the UNDRIP per se, one can conclude that it has become an unavoidable parameter of reference when dealing with indigenous peoples' rights, an increasingly robust legal instrument.